2016
DOI: 10.1128/mbio.01785-16
|View full text |Cite
|
Sign up to set email alerts
|

Identification of YbeY-Protein Interactions Involved in 16S rRNA Maturation and Stress Regulation in Escherichia coli

Abstract: YbeY is part of a core set of RNases in Escherichia coli and other bacteria. This highly conserved endoribonuclease has been implicated in several important processes such as 16S rRNA 3′ end maturation, 70S ribosome quality control, and regulation of mRNAs and small noncoding RNAs, thereby affecting cellular viability, stress tolerance, and pathogenic and symbiotic behavior of bacteria. Thus, YbeY likely interacts with numerous protein or RNA partners that are involved in various aspects of cellular physiology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
78
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(87 citation statements)
references
References 63 publications
6
78
0
Order By: Relevance
“…Our findings suggest that the toxicity of HuYbeY expression in yeast is most likely not linked to its RNase activity, but rather to unfavorable or non-regulated interactions of HuYbeY with proteins or nucleic acids, ultimately affecting cell physiology. These observations are consistent with the notion that HuYbeY function in human cells must be directed and regulated by evolved partners as YbeY function is in bacteria [25] and are a first indication for the possible involvement of HuYbeY in human diseases that are associated with the dysregulation of cellular HuYbeY levels.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…Our findings suggest that the toxicity of HuYbeY expression in yeast is most likely not linked to its RNase activity, but rather to unfavorable or non-regulated interactions of HuYbeY with proteins or nucleic acids, ultimately affecting cell physiology. These observations are consistent with the notion that HuYbeY function in human cells must be directed and regulated by evolved partners as YbeY function is in bacteria [25] and are a first indication for the possible involvement of HuYbeY in human diseases that are associated with the dysregulation of cellular HuYbeY levels.…”
Section: Resultssupporting
confidence: 89%
“…Second, we recently showed that certain residues (e.g. D85) located in a 4-stranded beta-sheet outside of the active site are important for interactions between EcYbeY and ribosomal protein S11; these interactions with the ribosome were also found to be important for EcYbeY’s role in rRNA maturation and stress regulation [25]. In addition, bacterial YbeY proteins share structural similarities with the MID domain of Argonaute (AGO) proteins, consistent with the observed involvement of YbeY in both Hfq-dependent and Hfq-independent small-RNA regulation in bacteria [17,20,28].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…YbeY also interacts with ribosomal proteins Era and S11 in E . coli , providing further evidence for its involvement in rRNA processing (Vercruysse et al ., ; Ghosal et al ., ).…”
Section: Introductionmentioning
confidence: 99%